Effect of training load on sleep parameters and biochemical fatigue markers in elite swimmers - Surała, Olga; Malczewska-Lenczowska, Jadwiga; Sitkowski, Dariusz; Witek, Konrad; Słomiński, Paweł; Certa, Maciej; Madej, Dawid (Biology of Sport, 2023)
The effect of strenuous exercise on sleep patterns in swimmers is equivocal. Therefore, the purpose of the study was to describe possible changes in sleep parameters among elite swimmers subjected to different training loads(TL). Methods: Eighteen elite swimmers(8 females) were monitored acrosstwo high-volume preparatory 1–wk periods (P1, P2) and a lower-volume tapering 1–wk period (P3) before a major competition. Internal (the session rating of perceived exertion [sRPE]) and external TL (training duration and volume) were measured, along with several sleep indices (e.g., bedtime, get-up time, sleep time, wake after sleep onset [WASO]). Serum measurements of urea, creatine kinase (CK), testosterone and cortisol were taken before and after training sessions at the beginning (Mondays) and end (Fridays) of each micro cycle. Athlete TL decreased significantly in a stepwise manner from P1 to P2 and from P2 to P3. Of all sleep parameters, only significant differences in bedtime and get up time emerged (P3 > P1 and/or P2). Sleep duration (~6.3 h) or quality (WASO: 41–45 min) were also unaffected by TL. CK levels declined from P1 to P3 (d = -0.8), and from P2 to P3 (d = -0.6). Positive exercise-induced changes in CK were also seen in each training period. The other biomarkers did not show the same temporal or acute patterns. Irrespective of the TL, the monitored swimmers experienced insufficient and fragmented sleep across this study. Neither sleep quality nor quantity were affected by different magnitudes of TL. Among the biochemical markers of fatigue, baseline plasma CK activity best reflected the physiological response to TL.